Aligning Advances in Biodiesel Technology with the Needs of the Defense Community - Vikram Mittal; Elliot Lim (Eng)
The global transportation sector is transitioning towards renewable energy to combat climate change, with biodiesel playing a critical role. Significant research over the past decades has focused on enhancing biodiesel through novel feedstocks and production methods. The defense community, a major diesel consumer, is particularly interested in biodiesel to support national sustainability goals while also leveraging the benefits of the new technology, including the ability to produce biodiesel locally at the point of need. This paper sets out to review recent advances in biodiesel technology and aligning them with the needs of the defense communities. By doing so, this paper provides insight into the challenges, benefits, and technical feasibility for the two primary consumers of military diesel fuel—naval ships and ground vehicles. For naval applications, algae-based biodiesel shows promise due to its potential for local production near ports. Advances in genetic engineering and cultivation are crucial for increasing lipid content and reducing costs. Innovative methods such as microwave-assisted transesterification and artificial neural networks for optimization could further enhance economic viability. In military ground vehicles, locally produced biodiesel could sustain operations by minimizing supply chain dependencies. Efforts are ongoing to develop mobile production facilities and improve feedstock diversity and methanol-independent transesterification processes. Overall, advancements in biodiesel production from various feedstocks and innovative techniques are poised to significantly benefit the military sector, promoting sustainability and operational efficiency.